2010
DOI: 10.1590/s1516-35982010000300017
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento ingestivo e consumo de forragem por cordeiras em pastagem de milheto recebendo ou não suplemento

Abstract: RESUMO -Avaliaram-se o comportamento ingestivo e o consumo de matéria seca de cordeiras recebendo diferentes tipos de suplemento em pastagem de milheto (Pennisetum americanum (L.) Leeke). Foram utilizadas 24 cordeiras com peso inicial de 30,2 ± 2,6 kg, distribuídas em três estratégias alimentares: pastagem de milheto exclusivamente; pastagem de milheto e suplementação com farinha de mandioca; e pastagem de milheto e suplementação com glúten de milho. Os suplementos foram fornecidos na quantidade de 1% do PV. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
2
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
2
9
2
8
Order By: Relevance
“…Studies conducted with millet in the form of pasture showed satisfactory performance in animal feeding (Roman et al, 2008;Jochims et al, 2010;Pacheco et al, 2014). In these studies, the fresh matter was used for the determination of the mass of pasture.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted with millet in the form of pasture showed satisfactory performance in animal feeding (Roman et al, 2008;Jochims et al, 2010;Pacheco et al, 2014). In these studies, the fresh matter was used for the determination of the mass of pasture.…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Jochims et al (2010), estudos sobre os efeitos das condições de pastejo sobre o comportamento ingestivo, consumo de forragem e desempenho dos ruminantes são importantes para o manejo adequado do sistema de produção animal adotado.…”
Section: Introductionunclassified
“…For each gram of PF added to the concentrate, it was possible to replace 2.27 and 2.47 g of the concentrate in G5 and G10, respectively, compared with the CS. The increase in the roughage:concentrate ratio by the inclusion of PF in the diet is desirable, especially for ewes kept in feedlots, since it allows lowering respiration rate and rectal temperature, consequently reducing thermal stress, which may compromise the performance of animals (Jochims et al, 2010).…”
Section: Coefficient Of Variation In Plots (Supplement)mentioning
confidence: 99%